ANALYSIS OF PATTERNED SUBORDINATE CONJUNCTIONS (V-RU)TO (V-TA) IN JAPANESE NOVEL: ANALISIS KONJUNGSI SUBORDINATIF BERPOLA (V-RU)TO (V-TA) DALAM NOVEL BAHASA JEPANG - Poppy Rahayu; Yuniarsih Yuniarsih; Annisa Dara Mutia (LLDIKTI Wilayah X, 2022)
The aim of this study is to determine the type of verbs that can be placed before and after subordinate conjunctions to, relationship between both clauses, and grammatical meaning which is contained in the (V-ru)To (V-Ta) sentence pattern. This study uses a classification based on the theory of Tomomasu, et al and theory of Sunakawa, et al about to ta pattern’s meaning which is divided into four types, there are Kikkake (trigger), Hakken (discovery), Guuzen (coincidence), and Renzoku (continuation). This study uses the Simak method for collecting the data, and using Padan Referensial method for analysis the data. Based on the analysis result, it is found that the type of verbs that can be placed before and after subordinate conjunctions to are same. The difference is that sonzai wo arawasu doushi (existence verbs) and joutai wo arawasu doushi (verbs that express situation) can be placed after the subordinate conjunctions to. Both syntactically and semantically, it is found that the subordinate conjunctions to in Kikkake's meaning is to show a mutual influencing relationship and the existence of a presuppositional modality also explain the causal relationship between clauses. The Hakken’s meaning is to shows an explanatory relationship also shows the discovery in the second clause. The Guuzen’s meaning connects two unrelated events and shows the movement of the third person. The Renzoku’s meaning is to relate several activities carried out on the basis of the speaker’s wishes.